Home health monitoring around the time of surgery: qualitative study of patients’ experiences before and after joint replacement - Rachael Gooberman-Hill; Ashley W Blom; Sabrina Grant; Ian Craddock; Micheal Whitehouse (BMJ Open)
Objectives Hip and knee replacements are common major elective surgical interventions with over 200 000 performed annually in the UK. Not all patients achieve optimal outcomes or experience problems or delays in recovery. The number of patients needing these operations is set to increase, and routine clinical monitoring is time-consuming and resource-consuming for patients and healthcare providers; therefore, innovative evaluation of surgical outcomes is needed. The aim of this qualitative study was to capture the patient experience of living with a novel home monitoring sensing system during the period around joint replacement.Setting One secondary care hospital in the South West, UK.Participants 13 patients (8 female, 63–89 years) undergoing total hip or knee replacement enrolled into the study.Design Qualitative study with thematic analysis. The system remained in situ for up to 12 weeks after their surgery and comprised a group of low-powered sensors monitoring the environment (temperature, light and humidity) and activity of people within the home. Patients were interviewed at two timepoints: before and after surgery. Interviews explored views about living with the technology, its acceptability, as well as attitudes towards health technology.Results Three main themes emerged: installation of home-sensing technology on the journey to surgery, the home space and defining unobtrusiveness and pivotal role of social support networks.Conclusions Patients who agreed to the technology found living with it acceptable. A home-sensing system that monitors the environment and activity of the people in the home could provide an innovative way of assessing patients’ surgical outcomes. At a time characterised by reduced mobility, functional limitations and increased pain, patients in this study relied on informal and formal supportive networks to help maintain the system through the busy trajectory of the perioperative period.